Metoda Sił dla Termo-Lepkosprężystych Układów Prętowych - Jędrzejczyk, J. (Engineering Transactions, 1973)
The paper presents the equations of the method of forces for viscoelastic systems subject to the action of a non-stationary temperature field. The solution is found within the framework of linear viscoelasticity, thermo-mechanical coupling effects being disregarded. Rheological properties of the material are assumed to be independent from the temperature.